(untitled) (The Peerian Journal, 2022)
One of the important components of the development of the country’s economy is the increase in consumption by the population. The Credit Institute is a center for ensuring the solvency of different segments of the population. In addition, the growth of entrepreneurship in the country, the development of the industrial sector and nanotechnological production is also ensured by improving and strengthening production capacities, purchasing the latest equipment, creating new jobs for free qualified employees, which is ensured by attracting borrowed funds, i.e. through lending to legal entities and individuals.